2000
DOI: 10.1128/jvi.74.12.5577-5586.2000
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Human Immunodeficiency Virus Infection of Human Cervical Tissue and Inhibition by Vaginal Virucides

Abstract: Heterosexual transmission of human immunodeficiency virus (HIV) is the most frequent mode of infectionworldwide. However, the immediate events between exposure to infectious virus and establishment of infection are still poorly understood. This study investigates parameters of HIV infection of human female genital tissue in vitro using an explant culture model. In particular, we investigated the role of the epithelium and virucidal agents in protection against HIV infection. We have demonstrated that the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
262
0
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(284 citation statements)
references
References 40 publications
13
262
0
9
Order By: Relevance
“…Such prototypic non-primary R5 and X4 strains have been widely used to test the susceptibility to HIV infection of a range of tissues including the cervix, prostate gland, foreskin, and penis. 26,[31][32][33][34][35] With use of these two strains, we demonstrated that the human seminal vesicles are selectively infected by macrophage-tropic HIV-1 R5 ex vivo and release infectious virions. The R5 SF162 strain consistently replicated in the seminal vesicle tissues, as assessed by increased reverse transcriptase activity in seminal vesicle supernatants during culture, increased level of viral DNA in the explants, PBMC infection by the viral particles recovered from the infected seminal vesicle supernatants, and in situ detection of infected cells in the explants using immunohistochemistry for HIV p24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such prototypic non-primary R5 and X4 strains have been widely used to test the susceptibility to HIV infection of a range of tissues including the cervix, prostate gland, foreskin, and penis. 26,[31][32][33][34][35] With use of these two strains, we demonstrated that the human seminal vesicles are selectively infected by macrophage-tropic HIV-1 R5 ex vivo and release infectious virions. The R5 SF162 strain consistently replicated in the seminal vesicle tissues, as assessed by increased reverse transcriptase activity in seminal vesicle supernatants during culture, increased level of viral DNA in the explants, PBMC infection by the viral particles recovered from the infected seminal vesicle supernatants, and in situ detection of infected cells in the explants using immunohistochemistry for HIV p24.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, the explant supernatants collected at various times during culture did not trigger productive infection of PBMCs, and infected cells were not detected using immunohistochemistry. HIV-1 X4 restriction has been reported for different organs in vitro and inferred to be either a low number of CD4 ϩ CXCR4 ϩ target cells, 33 unfavorable cytokine environment (eg, high level of the CXCR4 ligand SDF-1 36 ), or lack 34 or suboptimal activation 26 of T lymphocytes inducing post-entry block. In the seminal vesicles, the small number of CD4 ϩ CXCR4 ϩ T lymphocytes in the explants and the marked decrease in expression of the CXCR4 transcript during culture are likely involved in X4 restriction, although additional mechanisms cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Although presently available in vivo models, including the tissue explant systems (1,9,15) and the human tissue xenograft model (16), can be used to factor the impact of the stratified vaginal epithelial structure into studies of microbicide cytotoxicity, these assays may be limited in scale by tissue sample size and availability. In vitro methodologies using readily available cell lines are better suited to reproducibly screen large numbers of agents for cytotoxicity as well as for effectiveness against HIV-1-infected cells of immune origin.…”
mentioning
confidence: 99%
“…Although preclinical, in vitro assays of immune and epithelial cell sensitivity to candidate microbicides are necessary steps in the development of a potential microbicide, in vitro assays may fail to predict a compound's in vivo activity (4,33). One approach previously thought to be a necessary prerequisite for defining the fidelity of in vitro assays was the use of tissues or cells of primary human origin to test candidate microbicides (1,15). However, compared to available human immune and epithelial cell lines, primary tissues and cells are more difficult to acquire and isolate, less convenient and more expensive to maintain, potentially contaminated with unwanted cell populations, and prone to donorspecific variation.…”
mentioning
confidence: 99%
“…It may also bind to CXCR4 and gp120, suggesting multiple mechanisms of inhibition (Huskens et al, 2009). In a formulation of microbicide, it protects human female genital tissues against HIV-1 infection (Greenhead et al, 2000). It also inhibits DC-mediated virus transfer in vitro (Teleshova et al, 2008).…”
Section: Synthesized Peptides and Polymersmentioning
confidence: 99%